Making Collaboration Work: Fostering Positive Experiences and Attitudes around Psychological Safety, Diversity, and the Value of Teamwork - Kathryn S. Plaisance; Christine Logel; Christopher Lok (Canadian Journal for the Scholarship of Teaching and Learning)
The ability to work well in a team is becoming increasingly important across disciplines and throughout the workplace, making it a valuable skill for students to develop. Evidence suggests that diverse perspectives can generate more innovative ideas and enhance critical thinking, but only if team members value diversity and share knowledge with one another. To foster students’ abilities to work well in diverse teams, we must teach them why collaboration is important and how to bring about its benefits. We describe a new interdisciplinary course designed with these goals, along with an evaluation of the degree to which students who take this course show changes in attitudes and beliefs around teamwork. The course emphasizes psychological safety—a measure of how safe a team is for interpersonal risk-taking. Research shows that psychological safety is an important predictor of team success and a key mechanism for incorporating diverse perspectives. We surveyed students at the start of the course, the end of the course, and just after the following term. At the end of the course, students reported increased psychological safety in their teams, more positive attitudes towards teamwork, and stronger beliefs that diversity is beneficial. At the end of the following term, students reported higher levels of psychological safety in their teams than before the course, and their attitudes about psychological safety and teamwork still remained more positive. We discuss implications of these findings for researchers studying student teamwork and for instructors who wish to introduce or improve collaborative experiences in their courses.